Is the pediatric sleep questionnaire sensitive for sleep-disordered breathing in children with complex chronic disease - GÖKDEMİR, YASEMİN; ERDEM ERALP, ELA (My University, 2023)
Purpose: Sleep-disordered breathing (SDB) is a disease defined by breathing or breathing irregularities while asleep. The current study examines the association between results of polysomnography (PSG) and the Pediatric Sleep Questionnaire (PSQ), and the specificity and sensitivity of the PSQ for obstructive sleep apnea (OSA) in patients with chronic illnesses. Methods: Demographic and clinical attributes, in addition to PSQ and PSG outcomes were examined retrospectively among patients who underwent polysomnography (PSG) at our facility between 2012 and 2021. Results: Of 745 patients included in the study, 462 (62%) were male. The median age was 81 months (34–151 months). 117 of the patients (15/8%) had chronic lung disease, and 80 (10.7%) had cerebral palsy. The most common indications for PSG were symptoms of OSA (n = 426; 57.1%). According to obstructive apnea-hypopnea index (AHI), 361 patients (48.5%) had normal PSG. The median PSQ score was 0.40 (0.22–0.57). The sensitivity and specificity of the PSQ were 71.8% and 40.4%, respectively, for individuals aged 2 to 18 years. Among the disease subgroups, the cerebral palsy group had the highest sensitivity of PSQ (88.8%) for diagnosis of OSA. Conclusion: Questionnaires for evaluating SDB are not sensitive or specific for identification of OSA in children with chronic conditions, and PSG remains the best method.
Keywords: Tıp; Dahili Tıp Bilimleri; Nöroloji; Cerrahi Tıp Bilimleri; Kulak Burun Boğaz; Sağlık Bilimleri; Medicine; Internal Medicine Sciences; Neurology; Surgery Medicine Sciences; Otolaryngology; Health Sciences; Klinik Tıp (MED); Klinik Tıp; KULAK BURUN BOĞAZ; KLİNİK NÖROLOJİ; Clinical Medicine (MED); CLINICAL MEDICINE; OTORHINOLARYNGOLOGY; CLINICAL NEUROLOGY; Nöroloji (klinik); Otorhinolaryngology; Neurology (clinical); Children; Chronic disease; Pediatric Sleep Questionnaire; Polysomnography